PRAKTIK SIDANG SENGKETA EKONOMI SYARIAH PADA MAHASISWA FAKULTAS SYARIAH IAIN PONTIANAK (STUDI PENGEMBANGAN LABORATORIUM PERADILAN SEMU FAKULTAS SYARIAH IAIN PONTIANAK) - Arif Wibowo (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2021)
Along with the development of Sharia Economic law, disputes arise, as for Law Number 3 of 2006 jo. Law Number 21 of 2008, the authority to adjudicate sharia economic disputes by litigation. While this non-litigation program provides students with the Islamic Economics Law and Family Law Faculty of Sharia IAIN Pontianak in addition to developing themselves. On this basis, researchers are interested in exploring the engineering of the Sharia Faculty curriculum. This research is a field research (field search) object of students participating in quasi-trial practice. This research is qualitative. juridical-sociological approach, observation and interview data collection techniques. Analysis of the data using descriptive analysis-analysis with a deductive pattern. research findings; The first curriculum engineering has been carried out by the faculty. The researcher found that the number of Islamic law knowledge enrichment courses was 55 credits, the legal science enrichment courses were 44 credits, a total of 155 credits total. Second, researchers have not found laboratory assistants and modules in the moot court laboratory, and have not used the e-court application of the Supreme Court of the Republic of Indonesia. Third, the researchers found that the students were proficient in convening, but had not fully explored the material of sharia economic disputes.